The Use of Family Systems Approaches By School Counsellors - Sawatzky, D. Donald; Eckert, Corinne; Ryan, Bruce R. (Canadian Journal of Counselling and Psychotherapy, 1993)
The purpose of this study was to explore effective family systems interventions employed by school counsellors in their work with students. Five school counsellors who had some exposure to family systems approaches to counselling but were not family therapists participated in the study. They participated in three group meetings where family systems models were reviewed. Their task was then to conceptualize some of their cases within a family systems framework and report on the interventions they used that they perceived as effective. They were subsequently interviewed individually within a Critical Incidents format. Findings revealed six main categories of systemic interventions perceived as effective within schools. Examples of interventions to illustrate each of the categories are included in this paper. Also included, is a summation of the counsellors' reaction to working in this way.